A Novel Cellulase Produced by a Newly Isolated Trichoderma virens - Rong Zeng; Xiao-Yan Yin; Tao Ruan; Qiao Hu; Ya-Li Hou; Zhen-Yu Zuo; Hao Huang; Zhong-Hua Yang (Bioengineering, 2016)
Screening and obtaining a novel high activity cellulase and its producing microbe strain is the most important and essential way to improve the utilization of crop straw. In this paper, we devoted our efforts to isolating a novel microbe strain which could produce high activity cellulase. A novel strain Trichoderma virens ZY-01 was isolated from a cropland where straw is rich and decomposed, by using the soil dilution plate method with cellulose and Congo red. The strain has been licensed with a patent numbered ZL 201210295819.6. The cellulase activity in the cultivation broth could reach up to 7.4 IU/mL at a non-optimized fermentation condition with the newly isolated T. virens ZY-01. The cellulase was separated and purified from the T. virens culture broth through (NH4)2SO4 fractional precipitation, anion-exchange chromatography and gel filtration chromatography. With the separation process, the CMC specific activity increased from 0.88 IU/mg to 31.5 IU/mg with 35.8 purification fold and 47.04% yield. Furthermore, the enzymatic properties of the cellulase were investigated. The optimum temperature and pH is 50 °C and pH 5.0 and it has good thermal stability. Zn2+, Ca2+ and Mn2+ could remarkably promote the enzyme activity. Conversely, Cu2+ and Co2+ could inhibit the enzymatic activity. This work provides a new highly efficient T. virens strain for cellulase production and shows good prospects in practical application.